SOCIAL-PSYCHOLOGICAL ATRIBUTES OF ENSURING GENDER EQUALITY IN EFFECTIVE FORMATION OF MANAGEMENT PERSONNEL RESERVE - Abdullajanova Dilnozakhon Sultanbekovna (Web of Journals Publishing, 2025)
In this sense, they are very important for reflecting the processes taking place in the modern world, and their main direction is the increasing humanism and the increasing demands for the spiritual development of the individual, which determines the relevance of research today. The presence of highly qualified specialists as part of the organization’s human resources allows for a significant reduction in personnel recruitment costs and, as a result, for their adaptation, as well as for creating a system for investing in personnel development. Such investments have a significant impact on staff motivation and help retain staff in the organization, which reduces the level of staff turnover, as well as reduces risks in the event of temporary absence of management personnel and other force majeure situations.
Keywords: Personnel policy, personnel reserve, qualification, masculinity, femininity, androgyny, subject, management, gender, integration, gender socialization, gender equality.